PENGARUH EKSTRAK RIMPANG KUNYIT (CURCUMA DOMESTICA VAL) METODE MASERASI DAN DEKOK TERHADAP PENURUNAN SUHU TUBUH TIKUS PUTIH (RATTU NORVEGICUS) YANG DIBERI VAKSIN DPT - Dewi, Kadek Kusuma (Coping: Community of Publishing in Nursing, 2014)
Turmeric rhizome is one of the herbal plant which can use for antipyretic. One of the chemical content inside turmeric rhizome which can use for fever treatment is flavonoid. Use of dekok extraction method already use for processing turmeric rhizome as antipyretic. Considering that flavonoid compound can't stand with heat, then it necessary to do Tumeric rhizome processing with maceration method. This study aims for know the differences in effect turmeric rhizome extract with maceration method and dekok to decrease white rat body temperature which given DPT vaccine. This study is experimental study with completely randomized design. The treatment group consists of turmeric rhizome extract maceration method dose 126 mg, dose 252, dose 378 mg, dekok method at dose of 2.4  gr/200 grBB and control negative are give aquades (3cc/200grBB).. Data Analysis with One Way Anova test shown significant differences (p:0.001 < ?:0,05) between treatment groups before and after the intervention. The results of the analysis with post hoc test show not significant difference between treatment groups (p:0.095 - 0.947 > ?:0,05).
Keywords: Turmeric Rhizome Extract, Antipyretic; Maceration; Dekok; DPT vaccine